Sectoral Composition of Foreign Direct Investment and External Vulnerability in Eastern Europe - Kinoshita, Yuko (IMF Working Papers; Working Paper, 2011)
In the run up to the global crisis, countries in Central Eastern and Southeastern Europe attracted large capital inflows and some of them built up large external imbalances. This paper investigates whether these imbalances are linked to the sectoral composition of FDI. It shows that FDI in the tradable sectors leads to an improvement of the external balance. We also find that the countries with large market size, good infrastructure, greater trade integration, and educated labor force are more likely to receive more FDI in the tradable sectors.